G protein-dependent inhibition of L-type Ca2+ currents by acetylcholine in mouse pancreatic B-cells. - Gilon, P; Yakel, J; Gromada, J; Zhu, Y; Henquin, J; Rorsman, P (1997)
1. The effect of acetylcholine (ACh) on voltage-dependent Ca2+ currents in mouse pancreatic B-cells was studied using the whole-cell configuration of the patch-clamp technique. 2. ACh (0.25-250 microM) reversibly and dose-dependently inhibited the Ca2+ current elicited by depolarizations from -80 mV to +10 mV. Maximal inhibition was observed at concentrations > 25 microM where it amounted to approximately 35%. The effect was voltage independent and prevented by atropine (10 microM) suggesting that it was mediated by muscarinic receptors. 3. The inhibitory action of ACh on the Ca2+ current was abolished when the cytoplasmic solution contained GDP beta S (2 mM) and became irreversible when the non-hydrolysable GTP analogue GTP gamma S (10 microM) was included in the pipette. This indicates the participation of G proteins in the inhibitory effect of ACh but pretreatment of the cells with either pertussis or cholera toxin failed to prevent the effect of ACh on the Ca2+ current. 4. ACh remained equally effective as an inhibitor of the whole-cell Ca2+ current in the presence of the L-type Ca2+ channel agonist (-)-Bay K 8644 and after partial inhibition of the current by nifedipine. Addition of omega-agatoxin IVA, omega-conotoxin GVIA or omega-conotoxin MVIIC neither affected the peak Ca2+ current amplitude nor the extent of inhibition produced by ACh. These pharmacological properties indicate that ACh acts by inhibiting L-type Ca2+ channels. 5. The inhibitory action of ACh on the B-cell Ca2+ current was not secondary to elevation of [Ca2+]i and ACh remained equally effective as an inhibitor when Ba2+ was used as the charge carrier, when [Ca2+]i was buffered to low concentrations using EGTA and under experimental conditions preventing the mobilization of Ca2+ from intracellular stores. 6. These results suggest that ACh reduces the whole-cell Ca2+ current in the B-cell through a G protein-regulated, voltage- and Ca(2+)-independent inhibition of L-type Ca2+ channels.